Pengaruh Citra Sekolah dan Kualitas Pelayanan terhadap Kepuasan orang tua pada Madrasah Ibtidaiyah Negeri 2 Probolinggo - Umami, Fitria; Priantono, Seger; Dhany, Umi Rahma (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This study intends to investigate, at MIN 2 Probolinggo, the influence of school image and service quality on student parent satisfaction. The kind of investigation done is quantitative using a causal associative technique. While parent satisfaction (Y) is the dependent variable in this study, school image (X1) and service quality (X2) are the independent variables. From a sample of 89 parents of fifth and sixth graders, data were gathered by questionnaires, interviews, and documentation. The results revealed that parental satisfaction is much influenced by school image and service quality. Independent variables clearly contribute significantly to the dependent variable according to multiple regression analysis. Reliability and validity tests reveal dependability of the research tools. This study offers schools a significant contribution to raise their image and service quality so enhancing parental satisfaction. Future studies should investigate other elements influencing parent satisfaction, such parental involvement in school events.